Metabolic reprogramming from glycolysis to fatty acid uptake and beta-oxidation in platinum-resistant cancer cells - Yuying Tan; Junjie Li; Guangyuan Zhao; Kai-Chih Huang; Horacio Cardenas; Yinu Wang; Daniela Matei; Ji-Xin Cheng (Nature Communications, 2022)
Metabolic reprogramming is associated with cancer initiation, progression and resistance to therapy. Here, the authors show that metabolic reprogramming from glycolysis to fatty acid uptake and beta-oxidation is associated with cancer-cell platinum-based chemotherapy resistance.